Analysis of Potential Sectors and Policy Priorities of Regional Economic Development in Maluku Province - Bayu Kharisma; Ferry Hadiyanto (Faculty of Economic and Business, 2019)
The development policy in Maluku Province cannot separate from the small islands that dominate the areas. Its central potentials are in the field of fisheries, agriculture, and mining. This research aims to analyze the potentials of the leading sector and to formulate policy priorities for regional development in Maluku Province. The research used in this research is Location Quotient (LQ), Growth-Ratio Model (MRP), Overlay, SWOT and Analytic Network Process (ANP). The results showed that in Maluku Province there are eight economic categories that have base sectors. The result of Growth-Ratio Model (MRP) shows that the sector with the highest average the ratio of growth in the study area (RPs) is mining and quarrying sector. Furthermore, Overlay analysis shows that government administration, defense, social security sectors are obliged to contribute to and the highest growth. The result of SWOT-ANP shows that policy priority in regional development is the acceleration of infrastructure development. JEL Classification: E01, H70, R11